Modeling, parameterization and damping optimum-based control system design for an airborne wind energy ground station power plant. (15th May 2018) - Pavković, Danijel; Cipek, Mihael; Hrgetić, Mario; Sedić, Almir
Highlights: Harnessing high-altitude winds overcomes limitations of ground-based systems. Due to airborne module trajectory, power production intermittence is likely. An ultracapacitor energy storage is sized for ground station load levelling. A comprehensive ground station control strategy is proposed. Control strategy is verified by means of detailed simulations. Abstract: This paper presents the results of modeling and parameterization of the high-altitude wind energy system ground station power-plant equipped with a generator/motor unit as a primary power source tethered to the airborne module via a winch system, an ultracapacitor energy storage system, and grid inverter connected to the common direct-current link. Consequently, a suitable ground station power plant control strategy is designed, comprising the generator/motor speed control and cable tension control system, direct-current link power flow coordination control, and grid-side inverter control strategy. Control system design is exclusively based on the damping optimum criterion which provides a straightforward way of closed-loop damping tuning. The effectiveness of the proposed ground station control strategy is verified by means of comprehensive computer simulations. These have pointed out to precise coordination of the winch electrical servodrive with the airborne module-related rope force control system and sustained power production during the airborne module ascending phase in the presence of high-altitude wind disturbances, and continuous power delivery to the grid-side inverter, facilitated by the utilization of ultracapacitor energy storage. This indicates rather robust behavior of the overall ground station control system under anticipated external disturbance conditions.